Comparative Genome Analysis of a Pathogenic Erysipelothrix rhusiopathiae Isolate WH13013 from Pig Reveals Potential Genes Involve in Bacterial Adaptions and Pathogenesis - Longsheng Yang (Veterinary Sciences, 2020)
Erysipelothrix rhusiopathiae is a common pathogen responsible for pig erysipelas. However, the molecular basis for the pathogenesis of E. rhusiopathiae remains to be elucidated. In this study, the complete genome sequence of the E. rhusiopathiae strain WH13013, a pathogenic isolate from a diseased pig, was generated using a combined strategy of PacBio RSII and Illumina sequencing technologies. The strategy finally generated a single circular chromosome of approximately 1.78 Mb in size for the complete genome of WH13013, with an average GC content of 36.49%. The genome of WH13013 encoded 1633 predicted proteins, 55 tRNAs, as well as 15 rRNAs. It contained four genomic islands and several resistance-associated genes were identified within these islands. Phylogenetic analysis revealed that WH13013 was close to many other sequenced E. rhusiopathiae virulent strains. The comprehensive comparative analysis of eight E. rhusiopathiae virulent strains, including WH13013, identified a total of 1184 core genes. A large proportion (approximately 75.31%) of these core genes participated in nutrition and energy uptake and metabolism as well as the other bioactivities that are necessary for bacterial survival and adaption. The core genes also contained those encoding proteins participating in the biosynthesis and/or the components of the proposed virulence factors of E. rhusiopathiae, including the capsule (cpsA, cpsB, cpsC), neuraminidase (nanH), hyaluronidase (hylA, hylB, hylC), and surface proteins (spaA, rspA, rspB). The obtaining of the complete genome sequence of this virulent strain, WH13013, and this comprehensive comparative genome analysis will help in further studies of the genetic basis of the pathogenesis of E. rhusiopathiae.